A Rare Frameshift Mutation of in CmACS7 Alters Ethylene Biosynthesis and Determines Fruit Morphology in Melon (Cucumis melo L.) - Jiyang Zhou; Xiaobing Ma; Qianqian Deng; Zhicong Zhong; Xuefei Ning; Li Zhong; Xianliang Zhang; Xianlei Wang (Plants, 2025)
Fruit shape diversity in melon is governed by complex genetic networks, with ethylene biosynthesis playing a pivotal yet poorly characterized role. In this study, we identified a rare CmACS7A57V/frameshift double mutant through fine mapping of the fsq2 locus. Ethylene-mediated ovary growth regulation has been completely lost in the CmACS7A57V/frameshift double mutant, driving a transition from elongated to spherical fruit. Transcriptome analysis was performed to clarify the core role of CmACS7 in the ethylene signaling pathway. The loss of CmACS7 function regulates key genes in the ethylene responsive factor, cytokinin signaling pathway, and auxin-related genes, resulting in an imbalance in hormone levels. This imbalance directly affects the coordination of cell proliferation and expansion and ultimately determines the fruit morphology. A genetic diversity analysis of public melon germplasm resources indicated that while the CmACS7A57V/frameshift mutation accounts for only 0.5% of the germplasm, it is strongly correlated with the round fruit phenotype and is important for breeding in Xinjiang. The results of this study suggest that CmACS7A57V/frameshift could be used as a molecular marker to accelerate the breeding of melon varieties with excellent fruit morphology and, at the same time, reveal the coevolutionary significance of this gene in the domestication of Cucurbitaceae crops.